Cortisol and Estradiol Profile in Cross-bred Ettawa Does: The Effects of Body Condition Scoring (BCS). - Puji Astuti; D. Tri Widayati; S. Sunendar; K. Suharto; Asmarani Kusumawati; A. Junaidi (Indonesian Journal of Biotechnology, 2008)
Body Condition Scoring (BCS) is an estimation of the muscle and fat development of an animal. Thin ewes that are fighting to maintain their own body weight and low concentration of cortisol are not able to ovulate as ewes in a more desirable condition due to lack of oestradiol concentration. The aims of this research are to monitor the cortisol and oestradiol profile in Cross-bred ettawa does and to determine effect of BCS on the cortisol and oestradiol profile. Eight does were used in this research. These animals were devided equally into 2 groups based on Body Condition Scoring (BCS), namely BCS 2, which body weight range between 25-30 kgs as group I ( >n=4 ) and BCS 3 which consists of ettawa with body weight range between 33-40 kg as group II ( n=4 ). All animals were synchronized using implant of CIDR and PGF2alpha. Blood from jugular vein were collected every 3 and 6 hours as soon as oestrus until 72 hours. Serum contained cortisol and oestradiol then assayed using ELISA method. Cortisol and oestradiol concentrations were compared between groups by T test. The results showed that average concentration of cortisol is 47.17 ± 42.19 ng/mL for BCS 2 and 112.40±74.41ng/mL for BCS 3 (P<0.05), whereas concentration of oestradiol is 72.25±30.62 pg/mL for BCS 2 and 145.72±100.18 pg/mL for BCS 3 (P<0.05).  Either cortisol or oestradiol have very synchronized wave except 2 of animals from BCS 2 (50%), which has tendency to suppress each other. It was concluded that profile of cortisol and oestradiol hormone have a very similar pattern, and BCS can affect hormone profile.